Prediksi Potensi Keterlambatan Pembayaran Biaya Kegiatan Sekolah Menggunakan Algoritma Naïve Bayes - Solehan, Solehan; Sugiarto, Sugiarto; Mahdiana, Deni; Kharmytan, Yan Baktra (Universitas Budi Darma, 2024)
Tuition fees are one of very important component in the implementation of education and school development, because tuition fees are the main requirement to be able to implement school programs that have been designed in the one school year activity plan, apart from that, school fee is also used for maintenance or development of school facilities and infrastructure. Cempaka Vocational School is a private school in Central Jakarta, region two which requires its students to pay school activity fees by paying for each activity (7 days before the activity takes place) or in installments every month (total activity costs for one year divided by twelve ). Meanwhile, based on data obtained from the school treasurer, there were 23.2% arrears in the 2020/2021 school year and 38.7% arrears in the 2021/2022 school year (The data used in this research was taken from student payment data for the 2020/2021 and 2021/2022 school years ) which has not been resolved by students, this will become a big problem for Cempaka Vocational School if a solution is not immediately found to overcome this problem. The aim of this research is to build a prediction system using the Naïve Bayes method which will produce an accurate or late classification in paying school activity fees to be used as a recommendation in policy making and finding solutions early on so that there are no delays in paying school fees by students. /i. The results of this research produced an accuracy of 70.83%, precision of 70.59% and recall of 85.71 so that it could predict delays in school activity costs according to the needs of Cempaka Vocational School.